Concejo abierto, open government data in Bogotá's Council (2017)
Bogotá's government is divided into the Town Hall, led by the Mayor, and the Council, divided into three commissions. These two entities have huge tensions between them because they must keep control over the other and function independently. Currently, the Town Hall employs a big team to inform on any occurrence in the Council, but this team has been lagging due to their poor system. This paper presents Concejo Abierto, a system that tries to solve this problem by automatically organizing the information inputted. First, we show the bottleneck inside the Town Hall that the system aims to solve then we explain Open Government Data. Then, we show the process taken to create the system, which included interviews with the stakeholders and a deep data dive to the current data-store. Last, we show the result of the work which includes the product and perspective change in the team. You may find Concejo Abierto at https://concejoabierto.co